2018
DOI: 10.1261/rna.064881.117
|View full text |Cite
|
Sign up to set email alerts
|

Strong conservation of inbred mouse strain microRNA loci but broad variation in brain microRNAs due to RNA editing and isomiR expression

Abstract: Diversity in the structure and expression of microRNAs, important regulators of gene expression, arises from SNPs, duplications followed by divergence, production of isomiRs, and RNA editing. Inbred mouse strains and crosses using them are important reference populations for genetic mapping, and as models of human disease. We determined the nature and extent of interstrain miRNA variation by (i) identifying miRNA SNPs in whole-genome sequence data from 36 strains, and (ii) examining miRNA editing and expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 77 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…Finally, post-transcriptional processing of miRNAs can generate nucleotide changes at any position of the sequence by RNA processing enzymes, such as A-to-I editing by ADAR enzymes [30]. The specific function of isomiRs is still not well understood, but multiple studies have suggested a context-specific effect of isomiRs on gene regulation [26,28,31,32]. This is further supported by the fact that different isomiRs from the same mature miRNA can target virtually non-overlapping sets of transcripts [10,[33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, post-transcriptional processing of miRNAs can generate nucleotide changes at any position of the sequence by RNA processing enzymes, such as A-to-I editing by ADAR enzymes [30]. The specific function of isomiRs is still not well understood, but multiple studies have suggested a context-specific effect of isomiRs on gene regulation [26,28,31,32]. This is further supported by the fact that different isomiRs from the same mature miRNA can target virtually non-overlapping sets of transcripts [10,[33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Whether the relative frequency of classic vs non-classic editing in sperm may also be associated with APOBEC3A and impact bull fertility in cattle warrants future investigation. Furthermore, ADAR A > I editing has been previously described as the major driver of seed polymorphisms in the mouse brain, accounting for about 40% of changes within the seed [84]. This finding seems to be far from general, and in bull sperm G > A and C > U transitions are the most frequent changes within the seed.…”
Section: Isomirs: An Underexplored Diversitymentioning
confidence: 97%
“…Fueled by the advent of deep sequencing technologies, growing evidence has emerged that mature miRNAs undergo important post-transcriptional modifications [22][23][24][25][26]. These include nucleotide substitutions (miRNA editing) [27,28], 3′ adenylation or urydilation by terminal nucleotidyl transferases [29,30], shortening of their 3′ end by poly(A)-specific ribonuclease [31], and, more rarely, shifts in their 5′ start sites [24].…”
Section: Introductionmentioning
confidence: 99%